2021 Comprehensive Surveillance Review : Background Paper on The Surveillance Priority Ensuring Economic Sustainability. (Policy Papers; Policy Paper, 2021)
Ensuring economic sustainability is key to achieving the IMF's surveillance mandate of maintaining present and prospective balance of payments and domestic stability, assuring orderly exchange arrangements, and promoting a stable system of exchange rates. A good understanding of issues related to economic sustainability is thus essential for the IMF to provide effective surveillance and policy advice, while it requires a broad perspective and a long time horizon. With respect to the IMF's surveillance mandate, the principle of macro-criticality, which guides the IMF's engagement with its members, is sufficiently flexible and broad, allowing the IMF to cover issues related to economic sustainability. At the same time, given the wide range of issues that are related to economic sustainability, IMF surveillance needs to be selective and focused, with the choice of issues made on a case-by-case basis, considering country circumstances. It also needs to leverage the expertise of other institutions when necessary. The IMF and other institutions have advanced work to enhance analytical frameworks and indicators related to economic sustainability, and this should continue.